Upaya Penyuluh Agama dalam Pemberantasan Buta Aksara Al-Quran pada Anak di Desa Ujong Tanoh Darat Kec. Meureubo Kab. Aceh Barat - Sri Darlina; Kumalasari, Reni (Prodi Pengembangan Masyarakat Islam STAIN Teungku Dirundeng Meulaboh, 2024)
Reading the Quran is a must for Muslims from the past until now. However, the reality is that currently there are still many people who cannot recognize the hijaiyah letters and read the Koran well. In order to minimize the existence of Al-Qur'an illiteracy, the Ministry of Religion, through Islamic Religious Counselors, guides the learning of the Al-Qur'an to children through a program to eradicate Al-Qur'an illiteracy in various areas, including in Ujong Tanoh Darat Village. This research aims to determine the efforts made by Islamic religious instructors in eradicating Al-Qur'an illiteracy among children in Ujong Tanoh Darat Village. This research uses a qualitative descriptive approach with data collection techniques in the form of observation, interviews, and documentation. The results of this research show that, first, the efforts made by religious instructors in eradicating Al-Qur'an illiteracy in Ujong Tanoh Darat Village are: 1. Holding iqra' and Al-Qur'an level learning; 2. Providing awareness to the public about the importance of studying the Koran; and 3. Evaluate the reading of the Al-Qur'an. Second, the supporting factors for religious instructors' efforts in carrying out this program are the enthusiasm of children to take part in Al-Qur'an learning, support from village officials, and monitoring from the sub-district KUA. Meanwhile, the inhibiting factors are technological developments, lack of facilities and infrastructure, and the low salaries for Islamic Religious counselors.